Peptide aptamers define distinct EB1- and EB3-binding motifs and interfere with microtubule dynamics. - Le?niewska, K.; Warbrick, E.; Ohkura, H. (Molecular Biology of the Cell, 2014)
EB1 is a conserved protein that plays a central role in regulating microtubule dynamics and organization. It binds directly to microtubule plus ends and recruits other plus end-localizing proteins. Most EB1-binding proteins contain a Ser-any residue-Ile-Pro (SxIP) motif. Here we describe the isolation of peptide aptamers with optimized versions of this motif by screening for interaction with the Drosophila EB1 protein. The use of small peptide aptamers to competitively inhibit protein interaction and function is becoming increasingly recognized as a powerful technique. We show that SxIP aptamers can bind microtubule plus ends in cells and functionally act to displace interacting proteins by competitive binding. Their expression in developing flies can interfere with microtubules, altering their dynamics. We also identify aptamers binding to human EB1 and EB3, which have sequence requirements similar to but distinct from each other and from Drosophila EB1. This suggests that EB1 paralogues within one species may interact with overlapping but distinct sets of proteins in cells.